Penerapan Media Pembelajaran Berbasis Educaplay untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran SKI - Syifa Nur Fauziah; Masripah Masripah; Asep Tutun Usman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effect of implementing learning media based on Educaplay in improving students' learning outcomes in the subject of Islamic Cultural History (SKI). This research applies a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The study involved an experimental class with 17 students and a control class with 17 students. Data were collected through observation sheets on the implementation of learning as well as pre-test and post-test consisting of 16 questions. Data analysis included descriptive tests, normality tests, homogeneity tests, hypothesis tests, and N-Gain tests. Research findings show that the observation of the implementation of Educaplay media falls into the good/feasible category, with an observation score of 83 for teachers and 79 for students. Furthermore, the average score of the experimental class increased from 40.47 to 86.53, outperforming the control class which only increased from 47.94 to 60.24. The results of the independent sample t-test obtained a significance value of 0.001 < 0.05, which confirms the rejection of H0 and acceptance of Ha. In addition, the N-Gain of the experimental class reached 0.78 with a high category compared to the control class which was only 0.23 with a low category. It can be concluded that Educaplay media significantly influences the improvement of student learning outcomes in the Islamic Cultural History subject